High-water-resistance PVA separation membrane, high-water-resistance PVA composite membrane as well as preparation method and application of high-water-resistance PVA separation membrane

The crosslinking network structure is formed by reacting PVA with organic acid esterification, which solves the problem of PVA film being easily swelled under high temperature conditions, significantly improves its water resistance and stability, and uses green reagents to achieve protection of the health of operators.

CN119896985APending Publication Date: 2025-04-29CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311400700.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-26
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

Existing PVA membranes are prone to swell during steam penetration or high-temperature penetration vaporization, resulting in sharp deterioration or failure of membrane separation performance. In addition, existing modification methods such as chemical crosslinking using aldehydes pose a potential threat to the health of operators.

Method used

By esterifying PVA with organic acids such as eg eg, citric acid, tartaric acid and malonic acid, a crosslinking network structure is formed, the water resistance of the PVA film is improved, and green reagents are used to reduce the harm to the operator.

Benefits of technology

It effectively improves the water resistance and stability of PVA film, slows down or eliminates the stability problems caused by swelling, improves the selectivity of water, is suitable for the separation of alcohol-water systems, and has a simple and environmentally friendly preparation method.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004515167700000101
    Figure BDA0004515167700000101
  • Figure BDA0004515167700000111
    Figure BDA0004515167700000111
Patent Text Reader

Abstract

The invention relates to the technical field of separation membranes, and provides a high-water-resistance PVA separation membrane, a high-water-resistance PVA composite membrane as well as a preparation method and application of the high-water-resistance PVA separation membrane and the high-water-resistance PVA composite membrane. The PVA separation membrane with high water resistance is prepared by esterification reaction of PVA and organic acid, and the organic acid comprises at least one of oxalic acid, citric acid, tartaric acid and malonic acid. According to the high-water-resistance PVA separation membrane and the high-water-resistance PVA composite membrane provided by the invention, organic acid is adopted to perform esterification crosslinking on PVA, so that the water resistance of the PVA membrane is effectively improved, and the high-water-resistance PVA separation membrane can also have good water-resistance stability even under the condition that annealing treatment is not performed; and compared with a PVA membrane, the water selectivity is improved, and the membrane can be used for separating mixtures such as an alcohol-water system and the like. The preparation method is simple and easy to operate, and can be directly applied to industrial mass production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of separation membranes, and more specifically to a highly water-resistant PVA separation membrane, a highly water-resistant PVA composite membrane, and a preparation method and application thereof. Background Art

[0002] Pervaporation or steam permeation is a new type of membrane separation technology. In this process, the raw material mixture is separated and purified through a permeable membrane, thereby separating the organic matter from the mixture with water. It has the characteristics of small equipment size, energy saving, high separation efficiency, and no secondary pollution. In the process of steam permeation, hydrophilic membranes are generally used as membrane materials, such as polyvinyl alcohol membranes, chitosan membranes, polyimide membranes, cellulose acetate membranes, and polysulfone membranes. Among them, polyvinyl alcohol (PVA) has attracted widespread attention due to its low price, easy availability of raw materials, high hydrophilicity, good pollution resistance, and excellent film-forming properties. In particular, PVA has the properties of resistance to organic pollution and chlorine resistance, which can overcome the biggest challenges faced by commercial polyimide reverse osmosis membranes at present, making PVA membranes stand out among many membrane materials (such as polyimide membranes and polyolefin membranes), and have obvious advantages in subsequent industrialization and large-scale applications, so it is highly favored.

[0003] Although PVA membrane has the above-mentioned performance advantages, its application range is limited to a certain extent due to its shortcomings such as poor water resistance, low heat resistance and creep. In particular, the characteristic of PVA being easily soluble in hot water makes PVA membrane prone to swelling or even dissolution during steam permeation or pervaporation at a higher temperature, thereby destroying the permeation membrane structure and reducing the selective separation of the membrane. In order to overcome the effects of the swelling phenomenon such as the rapid deterioration of membrane separation performance and even failure, it is necessary to modify the PVA membrane in the hope of fundamentally solving its water resistance problem. PVA membrane modification methods include physical modification methods (such as blending, coating, doping, etc.) and chemical modification methods (such as surface grafting, cross-linking, etc.). In the prior art, aldehydes are used to react with PVA to form acetals, and chemical cross-linking is performed to improve water resistance stability, but aldehydes are very harmful to the body and will cause harm to the safety and health of production operators. Summary of the invention

[0004] The purpose of the present invention is to provide a highly water-resistant PVA separation membrane, a highly water-resistant PVA composite membrane and a preparation method thereof, so as to solve the technical problem in the prior art that the membrane separation performance of the PVA membrane deteriorates sharply or even fails due to swelling.

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] In a first aspect, the present invention provides a highly water-resistant PVA separation membrane, which is prepared by an esterification reaction between PVA and an organic acid, wherein the organic acid comprises at least one of oxalic acid, citric acid, tartaric acid and malonic acid.

[0007] In the present invention, the carboxylate in the organic acid will undergo an esterification reaction with a large number of hydroxyl groups in PVA (polyvinyl alcohol) to form a cross-linked network structure, which greatly reduces the H bonds of unreacted hydroxyl groups in the PVA chain, reduces its hydrogen bonding with water molecules, and slows down or eliminates the stability problem caused by swelling during long-term use. In addition, organic acids such as oxalic acid and citric acid are green reagents and will not endanger the health and safety of operators like aldehydes, which is also of great significance at a time when environmental protection is becoming increasingly stringent.

[0008] According to some embodiments of the present invention, the mass ratio of PVA to organic acid is 100:(3-20), for example, it can be 100:3, 100:5, 100:6, 100:8, 100:9, 100:10, 100:11, 100:11.5, 100:12, 100:12.5, 100:14, 100:15, 100:16, 100:18, 100:19, 100:20, etc.

[0009] According to some embodiments of the present invention, the mass ratio of the PVA to the organic acid is 100:(10-20).

[0010] According to some embodiments of the present invention, the esterification reaction of PVA and organic acid specifically includes: adding PVA to water to obtain a PVA solution, adding an organic acid to a solvent to obtain an organic acid solution; mixing the PVA solution and the organic acid solution to form a film, and then performing heat treatment.

[0011] In a second aspect, the present invention provides a highly water-resistant PVA composite membrane, comprising a support layer and the highly water-resistant PVA separation membrane described in the first aspect.

[0012] In the highly water-resistant PVA composite membrane provided by the present invention, the support layer is responsible for providing necessary mechanical properties, especially strength or pressure shock; the highly water-resistant PVA separation membrane plays a role of separation or purification.

[0013] According to some embodiments of the present invention, the support layer is selected from at least one of porous PVDF, porous ceramics, porous metals, and porous glass.

[0014] In the present invention, the support layer is generally a thin plate or a thin layer structure.

[0015] In a third aspect, the present invention provides a method for preparing the highly water-resistant PVA composite film described in the second aspect, comprising: adding PVA to water to obtain a PVA solution, and adding an organic acid to a solvent to obtain an organic acid solution; mixing the PVA solution and the organic acid solution to form a film on a support layer, and then performing heat treatment to obtain the highly water-resistant PVA composite film.

[0016] After PVA is added to water, it will wet, swell, swell infinitely, and dissolve in sequence, eventually forming a PVA solution. PVA dissolution takes more time, and if necessary, it can be heated during the process to speed up the dissolution process, and then cooled to room temperature after it is completely dissolved.

[0017] According to some embodiments of the present invention, the solvent includes ethanol and an aqueous solution thereof.

[0018] According to some embodiments of the present invention, the film forming is performed at room temperature.

[0019] Film formation at room temperature simplifies the film formation process and saves a lot of energy and material consumption compared to methods such as hot stretching or thermal phase change. In addition, room temperature film formation greatly simplifies workshop conditions, facilitates production operations, and significantly saves production costs; and mild film formation conditions are beneficial to the physical and mental health of production technicians, avoiding damage to personnel health caused by high temperature and high humidity.

[0020] Existing commonly used organic film-forming methods are all applicable to the preparation method of the highly water-resistant PVA composite film provided by the present invention, which not only facilitates mass production and reduces costs, but also can form membranes, membrane assemblies or membrane components of any configuration or shape, with a wide range of applicable scenarios and strong universality.

[0021] According to some embodiments of the present invention, the film forming method includes any one of scraping, spraying, rolling, roller coating, and dipping.

[0022] According to some embodiments of the present invention, the film thickness is 50 to 200 μm, preferably 80 to 120 μm.

[0023] According to some embodiments of the present invention, the heat treatment comprises drying at 40 to 60° C. The drying time may be 7 to 25 hours.

[0024] According to some embodiments of the present invention, the heat treatment includes drying at 40-60° C. and then annealing at 80-150° C., wherein the drying time may be 7-15 hours, and the annealing time may be 0.5-25 hours.

[0025] In a fourth aspect, the present invention provides the use of the highly water-resistant PVA separation membrane described in the first aspect, the highly water-resistant PVA composite membrane described in the second aspect, or the highly water-resistant PVA composite membrane prepared by the preparation method described in the third aspect in the field of pervaporation, especially in alcohol dehydration.

[0026] The beneficial effects of the present invention are at least:

[0027] The highly water-resistant PVA separation membrane and highly water-resistant PVA composite membrane provided by the present invention use organic acid to esterify and cross-link PVA, effectively improving the water resistance of the PVA membrane, and having good water resistance stability even without annealing treatment; and compared with the PVA membrane, the selectivity for water is improved, and can be used for separation of mixtures of organic matter and water such as alcohol-water systems. The preparation method adopted by the present invention is simple, easy to operate, and can be directly applied to large-scale industrial production. DETAILED DESCRIPTION

[0028] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain this patent in detail and do not limit the scope of protection of the present invention in any way.

[0029] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the raw materials, instruments and equipment used in the following examples, etc., can all be purchased on the market or can be obtained by existing methods; the reagent amounts, unless otherwise specified, are the reagent amounts used in conventional experimental operations; the experimental methods, unless otherwise specified, are all conventional methods.

[0030] The 1 part (part by weight) described in the various embodiments and comparative examples of the present invention may be any weight such as 10 g, 100 g, 1000 g, 10 kg, etc.

[0031] Example 1

[0032] 1) Weigh 1 part of PVA 1788 and dissolve it in 9 parts of water, fully wet it for 3 hours, then heat it while stirring, complete swelling, unlimited swelling, until it is fully dissolved at 90°C, and then cool it to room temperature to obtain a PVA aqueous solution; weigh 0.115 parts of oxalic acid (OA) and dissolve it in 1 part of ethanol to obtain an OA ethanol solution;

[0033] 2) slowly adding the OA ethanol solution obtained in step 1) into the PVA solution obtained in step 1), stirring at room temperature until the mixture is uniform, to obtain a film-forming solution; forming a film with the film-forming solution by a doctor blade method, specifically, forming a film on a commercially available PVDF base film with a nominal pore size of 0.1 μm using a 100 μm scalpel, to form a 100 μm thick wet film;

[0034] 3) The wet film obtained in step 2) is dried at 50° C. and annealed at 100° C. for 12 h and 20 h, respectively, to obtain an oxalic acid-crosslinked PVA composite film with high water resistance.

[0035] Example 2

[0036] 1) Weigh 1 part of PVA 1799 and dissolve it in 9 parts of water, fully wet it for 3 hours, then heat it while stirring, complete swelling, unlimited swelling, until it is fully dissolved at 95°C, and then cool it to room temperature to obtain a PVA aqueous solution; weigh 0.18 parts of oxalic acid (OA) and dissolve it in 1 part of ethanol to obtain an OA ethanol solution;

[0037] 2) slowly adding the OA ethanol solution obtained in step 1) into the PVA solution obtained in step 1), stirring at room temperature until the mixture is uniform, to obtain a film-forming solution; forming a film with the film-forming solution by a doctor blade coating method, specifically, forming a film on a commercially available PVDF base film with a nominal pore size of 0.1 μm using a doctor blade with a gap of 120 μm, to form a 120 μm thick wet film;

[0038] 3) The wet film obtained in step 2) is dried at 50° C. and annealed at 110° C. for 10 h and 16 h, respectively, to obtain an oxalic acid-crosslinked PVA composite film with high water resistance.

[0039] Example 3

[0040] 1) Weigh 1 part of PVA 1788 and dissolve it in 10 parts of water, fully wet it for 3 hours, then heat it while stirring, complete swelling, unlimited swelling, until it is fully dissolved at 90°C, and then cool it to room temperature to obtain a PVA aqueous solution; weigh 0.19 parts of citric acid (CA) and dissolve it in 1 part of ethanol to obtain a CA ethanol solution;

[0041] 2) slowly adding the CA ethanol solution obtained in step 1) into the PVA solution obtained in step 1), stirring at room temperature until the mixture is uniform, to obtain a film-forming solution; forming a film with the film-forming solution by a doctor blade method, specifically, forming a film on a commercially available porous glass base film with a nominal pore size of 0.1 μm by using an 80 μm scalpel, to form a wet film with a thickness of 80 μm;

[0042] 3) The wet film obtained in step 2) is dried at 50° C. and annealed at 110° C. for 12 h and 8 h, respectively, to obtain a citric acid cross-linked PVA composite film with high water resistance.

[0043] Example 4

[0044] 1) Weigh 1 part of PVA 1798 and dissolve it in 13 parts of water, fully wet it for 3 hours, then heat it while stirring, complete swelling, unlimited swelling, until it is fully dissolved at 95°C, and then cool it to room temperature to obtain a PVA aqueous solution; weigh 0.20 parts of citric acid (CA) and dissolve it in 2 parts of ethanol to obtain a CA ethanol solution;

[0045] 2) slowly adding the CA ethanol solution obtained in step 1) into the PVA solution obtained in step 1), stirring at room temperature until the mixture is uniform, to obtain a film-forming solution; forming a film with the film-forming solution by roller coating, specifically, using a non-linting wool roller, and forming a film on a commercially available porous glass base film with a nominal pore size of 0.1 μm, to form a wet film with a thickness of about 100 μm;

[0046] The wet film obtained in step 2) is dried at 50°C and annealed at 140°C for 10 hours and 2 hours, respectively, to obtain a citric acid cross-linked PVA composite film with high water resistance.

[0047] Example 5

[0048] The preparation method of the highly water-resistant PVA composite film is similar to that of Example 1, except that 0.115 parts of oxalic acid are replaced by 0.115 parts of malonic acid.

[0049] Example 6

[0050] The preparation method of the highly water-resistant PVA composite film is similar to that of Example 1, except that 0.115 parts of oxalic acid are replaced by 0.115 parts of tartaric acid.

[0051] Example 7

[0052] The method for preparing the highly water-resistant PVA composite film is similar to that of Example 1, except that the amount of oxalic acid is adjusted from 0.115 parts to 0.03 parts.

[0053] Example 8

[0054] The method for preparing the highly water-resistant PVA composite film is similar to that of Example 1, except that the amount of oxalic acid is adjusted from 0.115 parts to 0.06 parts.

[0055] Example 9

[0056] The method for preparing the highly water-resistant PVA composite film is similar to that of Example 1, except that the amount of oxalic acid is adjusted from 0.115 parts to 0.25 parts.

[0057] Example 10

[0058] The method for preparing the highly water-resistant PVA composite film is similar to that of Example 1, except that the amount of oxalic acid is adjusted from 0.115 parts to 0.30 parts.

[0059] Embodiment 11

[0060] The preparation method of the highly water-resistant PVA composite film is similar to that of Example 1, except that in step 3), the film is dried at 50° C. for 12 h only, and no annealing step is included.

[0061] Comparative Example 1

[0062] The preparation method of the PVA composite film refers to Example 1, except that 0.115 parts of oxalic acid are replaced by 0.115 parts of succinic acid.

[0063] Comparative Example 2

[0064] The preparation method of the PVA composite film refers to Example 1, except that 0.115 parts of oxalic acid are replaced by 0.115 parts of adipic acid.

[0065] Comparative Example 3

[0066] 1) Weigh 1 part of PVA 1788 and dissolve it in 9 parts of water, fully wet it for 3 hours, then heat it while stirring, complete swelling, unlimited swelling, until it is fully dissolved at 90°C, and then cool it to room temperature to obtain a PVA aqueous solution;

[0067] 2) forming a film of the PVA solution obtained in step 1) by a doctor blade method, specifically, forming a film on a commercially available PVDF base film with a nominal pore size of 0.1 μm using a 100 μm scalpel to form a 100 μm thick wet film;

[0068] 3) The wet film obtained in step 2) is dried at 50° C. and annealed at 100° C. for 12 h and 24 h, respectively, to obtain a PVA composite film.

[0069] Comparative Example 4

[0070] The preparation method of the PVA composite film refers to Comparative Example 3, except that in step 3), the film is dried at 50° C. for 12 h only, and no annealing step is included.

[0071] Performance evaluation of PVA composite membrane

[0072] The dimensional stability S, permeation flux J and separation coefficient α of the PVA composite membranes provided in the embodiments and comparative examples were tested, and the results are shown in Table 1.

[0073] The test methods for each performance parameter are as follows:

[0074] (1) Dimensional stability S:

[0075] S=(lj -l i ) / l i *100; where l i , l j The dimensions are before immersion in water and after removal from the immersion water.

[0076] The dimensional stability S is the dimensional stability of the PVA separation membrane after it is completely immersed in water for 100 hours, and the change rate of the membrane size before and after immersion is multiplied by 100. The deviation of the S value from the standard value of 100 represents the water resistance. The greater the deviation, the worse the water resistance of the separation membrane, and the less the deviation, the better the water resistance. An S value greater than 100 indicates swelling, and an S value less than 100 indicates shrinkage.

[0077] (2) Permeation flux J

[0078] J = condensate volume m / (membrane effective area S*test time t), unit: [g / m 2 h -1 ].

[0079] The test method of permeation flux J is as follows:

[0080] 1) Set the designated area (test area S = 13.2 cm 2 ) is placed in a membrane pool equipped with a porous support plate, laid flat on the porous support plate without wrinkles, and fixed and sealed with an O-ring;

[0081] 2) The feed liquid to be separated is contacted on one side of the separation membrane, and the feed liquid to be separated is circulated back and forth between the raw material tank and the membrane pool at a set temperature (RT = 30°C in this test) to prevent the concentration difference of the feed liquid from affecting the test results;

[0082] 3) Connect the liquid collecting pipe, cold well, vacuum pump and vacuum gauge in sequence on the other side of the separation membrane;

[0083] 4) After the separation liquid fully infiltrates the separation membrane, start calculating the test time t;

[0084] 5) Take out the collecting pipe from the cold well and seal both ends of it to isolate the vacuum system from the infiltration liquid;

[0085] 6) Weigh the amount of condensate collected in the collecting tube (m).

[0086] In this test, an aqueous solution with an isopropanol content of 90 wt% was used as the liquid to be separated; the pressure of the vacuum gauge was <10 mbar.

[0087] (3) Separation coefficient α

[0088] α=(Y A / YB ) / (X A / X B )=(Y A *X B ) / (Y B *X A ), where Y A , Y B respectively

[0089] is the composition of A and B in the condensate; X A , X B They are the A and B compositions of the liquid to be separated, and A and B represent water and isopropanol respectively.

[0090] The test method of separation coefficient α is the same as that of permeation flux.

[0091] Table 1 PVA composite film performance evaluation

[0092]

[0093]

[0094] It can be seen from the above test results that the highly water-resistant PVA composite membrane provided by the present invention has excellent dimensional stability by adding organic acids such as citric acid and tartaric acid to PVA for cross-linking reaction, and no obvious swelling is observed after 100 hours of immersion, and the permeation flux and separation coefficient are also very high. In addition, the highly water-resistant PVA composite membrane provided by the present invention has excellent dimensional stability even without annealing treatment, and no obvious swelling is observed after long-term immersion.

[0095] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.

Claims

1. A highly water-resistant PVA separation membrane, characterized in that: The highly water-resistant PVA separation membrane is prepared by esterification reaction between PVA and an organic acid, wherein the organic acid comprises at least one of oxalic acid, citric acid, tartaric acid and malonic acid.

2. The highly water-resistant PVA separation membrane according to claim 1, characterized in that The mass ratio of the PVA to the organic acid is 100:(3-20), preferably 100:(10-20).

3. A highly water-resistant PVA composite film, characterized in that: It comprises a supporting layer and the highly water-resistant PVA separation membrane according to claim 1 or 2.

4. The highly water-resistant PVA composite film according to claim 3, characterized in that: The support layer is selected from at least one of porous PVDF, porous ceramics, porous metals and porous glass.

5. The method for preparing a highly water-resistant PVA composite film according to claim 3 or 4, characterized in that: include: PVA is added to water to obtain a PVA solution, and an organic acid is added to a solvent to obtain an organic acid solution; The PVA solution and the organic acid solution are mixed to form a film on the support layer, and then heat-treated to obtain the highly water-resistant PVA composite film.

6. The preparation method according to claim 5, characterized in that: The solvent includes ethanol and an aqueous solution thereof.

7. The preparation method according to claim 5 or 6, characterized in that: The film formation is carried out at room temperature.

8. The preparation method according to any one of claims 5 to 7, characterized in that: The film forming method includes any one of scraping, spraying, rolling, roller coating and dipping.

9. The preparation method according to any one of claims 5 to 8, characterized in that: The heat treatment includes drying at 40 to 60°C; Alternatively, the heat treatment includes drying at 40-60°C first, and then annealing at 80-150°C.

10. Use of the highly water-resistant PVA separation membrane according to claim 1 or 2, or the highly water-resistant PVA composite membrane according to claim 3 or 4, or the highly water-resistant PVA composite membrane prepared by the preparation method according to any one of claims 5 to 9 in the field of pervaporation, especially in alcohol dehydration.

Citation Information

Patent Citations

  • Composite membrane for the separation of water and method for manufacturing same

    US20100084335A1

  • Pervaporation membranes and methods of use

    US7045062B1